2020
DOI: 10.3904/kjim.2019.269
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic efficacy of water-soluble coenzyme Q10 in an experimental model of tacrolimus-induced diabetes mellitus

Abstract: Background/Aims: Coenzyme Q 10 (CoQ 10) has antioxidant effects and is commercially available and marketed extensively. However, due to its low bioavailability, its effects are still controversial. We developed a water-soluble CoQ 10-based micelle formulation (CoQ 10-W) and tested it in an experimental model of tacrolimus (TAC)-induced diabetes mellitus (DM). Methods: We developed CoQ 10-W from a glycyrrhizic-carnitine mixed layer CoQ 10 micelle preparation based on acyltransferases. TAC-induced DM rats were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Oxidative hepatic damage and change in liver architecture with significant decrease in GSH concentration, inhibition of SOD and CAT activity, and increased MDA level have been previously reported in a liver toxicity model of rats [ 31 , 32 ], and a link between change in antioxidant status and liver histopathology owing to liver injury has been described [ 33 ]. Additionally, decreased activity of SOD and CAT, reduced GSH concentration, and increased MDA level have been suggested to be responsible for oxidative damage and apoptosis in TAC-induced diabetes mellitus in an animal model [ 34 ]. MDA reflects lipid peroxidation and plays a vital role on oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative hepatic damage and change in liver architecture with significant decrease in GSH concentration, inhibition of SOD and CAT activity, and increased MDA level have been previously reported in a liver toxicity model of rats [ 31 , 32 ], and a link between change in antioxidant status and liver histopathology owing to liver injury has been described [ 33 ]. Additionally, decreased activity of SOD and CAT, reduced GSH concentration, and increased MDA level have been suggested to be responsible for oxidative damage and apoptosis in TAC-induced diabetes mellitus in an animal model [ 34 ]. MDA reflects lipid peroxidation and plays a vital role on oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported the efficacy of CoQ 10 -W in Tac-induced diabetes mellitus [23], and this study ex-tended the evaluation of this effect to Tac-induced renal injury. The results of our study clearly demonstrate that CoQ 10 -W significantly improved renal function and histopathological parameters compared to that with CoQ 10 -L in a rat model of Tac-induced renal injury.…”
Section: Discussionmentioning
confidence: 89%
“…For this reason, we developed water-soluble CoQ10 (CoQ10-W) to improve its bioavailability [98]. We found that CoQ10-W may provide more benefits than conventional CoQ10 by diminishing injury in the pancreas [99] and UUO-induced kidney [24]. Table 2 summarizes the management of UUO-induced renal fibrosis using clinical conventional drugs.…”
Section: Coenzyme Q10mentioning
confidence: 99%